Oncogene expression in hepatocellular carcinoma and cells - Arbuthnot, Patrick Brian (My University, 2016)
An investigation has been made into aspects of the expression of oncogenes in normally dividing cells and in hepatoceilular carcinoma (Hee). HOC occurs commonly in Southern Africs, and thf1aetiology ·ofthis tumour lsaseccieted with hepatitis a virus (HBV) infection. c·erbA, c..mva and e-tos but not c~Ha..res mANA were elevatad in tumours and adjacent hepatic tissue from the same petiEJ;htswhen compared to normal liver. Amounts of Fos and MYQ prot~in in the liver tumour specimens were else raised. The"e was some correlation between the patients' serum a..fetoproteirt concentretlons, histological features of tumour differentiatic)t"l, c..mvc and c40s r.ixpression. expression of e-tas and c..myc has been reportec to be elevated after stimulation of cells to alvlde, ,'1$ occurs during liver r19ganeration. This was corroborated by the findin~ that c-mvc, c·fo~· and c-jun mRNA concentratlona "Jere increased it"! cultured 3T6 mouse fibroblasts following treatment with alkaline medium aa a mitogenlo stimulus. The time course of the expression of these oncogenes was similar to that reported after gro\l'l/th factor sttmulation, The H[~V X..gene ma\' be responsible for increased oncogene expression it' YCC as a result of its documented trans activating properties. This vi!'a~ gene is unusual in that it has a codon preferanc";which is similar to that of eukarvotic ceU genes. Also HBV may ha'V& evolved from ti similar ancestral virus to that giving rise to retroviruses. These ideas suggest that the HBV X·gene is a viral oncogene derived from a host homologue. Low stringency Northern brot hybridisation using a X-gene probe denlonstrated a murine transcrlpt in heart and thymus. Attempts to isolate the sequence from mouse heart and thymus eDNA libraries ware unsuccessful despite ext,~n$jve screening with sensitive probes (SP6 palymerfjsa and peR fab(':.lUed X~gen~~fragments). Conserved X~gene \ . I sequences were also used fot the desigr:Jof primers in .~.peR bas£'d method " . II aimed at isolating a mammalian sequence. No sinnificant sequsnce \\ homology was found bet\lveen the HBVI\X..gene and Ol\A ampllfle'd from \1 l! gen(llmic and eDNA I1br'srytemplate sou~\pes.The peR preducts ttppeared to have been artef.,ots of arnplWaation. ~~n'IJreto detect the hQrtll.)logous gene may have resu~ted from poo' complS,JIlentarity between the VIral ant! \\ mammalian secuencec, 1\ \\ Non..~pecific amplification is commonly enct~unter&d when u$1110 PCli'. A qtJick asvmmatrlc re·ampW~catj(ii1 method I,?ssed on eXUOSilin of an " interm.uly' hybrfdising X·gelllapfimar we! davisQ\j to confirm FICRprOdu(,ts. The l"n1ithodwas specific irlthat "ver~ single bas~ mlsmatohe$ betwsen the internal primer and tem1>late re;.,ultad in fatJut~ of dete(;tabla \tUim$f extension.
Thesis is submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science (Biochemistry), University of the Witwatersrand, Johannesburg, 1992
Keywords: Liver--Cancer; Gene expression; Oncogenes; Cell division; Hepatitis B virus